SiC power module design performance, robustness and reliability - Castellazzi, Alberto; Irace, Andrea (The Institution of Engineering and Technology, 2021)
Wide Bandgap semiconductor devices offer higher efficiency, smaller size, less weight, and longer lifetime, with applications in power grid electronics and electromobility. This book describes the state of advanced packaging solutions for novel wide-band-gap semiconductors, specifically silicon carbide (SiC) MOSFETs and diodes
Keywords: Wide gap semiconductors.; Silicon carbide.; elektronické knihy; electronic books